Perinatal asphyxia and its associated factors among perinatal mortality in Kelantan from 2020 – 2022. - Mohamad, Izyan Auni (Universiti Sains Malaysia, 2024)
Background of the study: Perinatal mortality remains a significant public health concern globally, with neonatal deaths accounting for nearly half of all under-five deaths. Perinatal asphyxia is a major contributor to perinatal mortality, especially in low- and middle-income countries. Perinatal asphyxia is the second largest preventable cause of perinatal death in Malaysia. However, the specific burden and factors associated with this perinatal asphyxiation death are still unclear in Malaysia in general and in Kelantan in particular. Objective: This study aimed to determine the proportion of perinatal asphyxia and its associated factors among perinatal mortality cases in Kelantan, Malaysia, from 2020 to 2022. Methodology: This cross-sectional study was conducted between December 2023 and June 2024 based on a retrospective review of perinatal mortality data by the Kelantan State Health Department from 2020 to 2022. Secondary data for this study were obtained from the Stillbirth and Under-five Mortality Notification System and Stillbirth and Under-five Mortality Investigation Form. A total of 397 deaths were selected using a simple random sampling method using Microsoft Excel. Sociodemographic, obstetric, and intrapartum factors have been taken from records and analysed using descriptive analysis, simple logistical regression and multiple logistic regression to identify factors associated with perinatal asphyxia. (aOR=2.70, 95% CI : 1.18-6.22, p=0.019), inadequate antenatal follow up or unbooked mothers (aOR=2.95, 95% CI : 1.66-5.22, p<0.001), late preterm birth (aOR=2.49, 95% CI : 1.20-5.18, p=0.014), and caesarean section deliveries (aOR=2.52, 95% CI : 1.51-4.21, p<0.001) were significantly associated with perinatal asphyxia. Conclusion: Perinatal asphyxia accounts for a substantial proportion of perinatal mortality in Kelantan, Malaysia. Maternal factors, such as non-Malay mothers, mothers attending inadequate antenatal follow-up or unbooked mothers; late premature births and caesarean births are significantly associated with perinatal mortality caused by perinatal asphyxia. Identifying these related factors can help improve future strategies and interventions such as improving antenatal care, improving intrapartum management, and strengthening the ability to provide health care. It can also help to improve service quality and reduce the number of deaths caused by perinatal asphyxia across the country. Further research is needed to explore the underlying causes and develop context-specific strategies to address the high burden of perinatal mortality in Kelantan. Results: Out of 397 perinatal mortality cases reviewed, the proportion of perinatal asphyxia was 25.9%. The multivariate analysis showed that non-Malay mothers